'No one listens to us … ' COVID-19 and its socio-spatial impact on children and young people in Germany. Issue 4 (4th July 2022) - Million, Angela
ABSTRACT: The handling of COVID-19 in Germany has shown that children, young people and families are not a top priority. Available studies identify a significant socio-spatial impact in this regard. Limits and conflicts can be discerned due to domestic concentration, wh blurs times and spaces and highlights the dependency of families in Germany on social infrastructure. During lockdown, there is a rise in digitalized activities, but homeschooling reveals a digital divide and reinforces the existing lack of equal opportunities for students. While new spatial movements create better spaces for children, young people face an ongoing struggle with the limitations created by the pandemic.